The entrapment, manipulation, and transformations of inorganic materials at the nanoscale - Norman, Luke Thomas (2022)
The work presented in this thesis investigates demonstrates the unique ability of single-walled carbon nanotubes (SWNTs) to be able to use their interior channel as a nano test tube to study the structure and composition of inorganic materials at the nanoscale, as well as conduct chemical reactions within. Each system presented was strategically designed, and studied using a holistic analytical approach which combined a range of electron microscopy, and spectroscopic techniques and revealed nanomaterials with novel structures, compositions, and coordinations that are not possible to obtain using bulk synthetic techniques. The targeted synthesis of ultrathin rhenium disulfide nanoribbons was conducted within SWNTs using a stepwise methodology. Aberration-corrected high-resolution transmission electron microscopy (AC-HRTEM) was able to resolve the twisted structure of the synthesised nanoribbons, and the strong interactions between the host and guest resulting in an elliptical distortion of the SWNT. The differences of the two surface sites of SWNTs, the concave and convex, were examined by conducting a stepwise series of chemical reactions of osmium compounds on each site simultaneously. AC-HRTEM revealed that the concave surface produced size-templated sub-nm nanowires with reduced coordination and stabilised by the SWNT surface, whilst the convex surface produced larger nanoparticles with higher coordinations and novel shell structures stabilising the high number of dangling bonds. The insertion of thiomolybdate-based clusters into SWNTs was found to proceed by coulombic attraction initiated by electron donation from the nanotubes to the clusters, as demonstrated by Raman spectroscopy. Furthermore, their structure and orientations observed in AC-HRTEM were determined by correlation of projections with a rotation series of TEM simulations, and their fast translational motion was captured between sequential images. The reaction of the clusters with iodine resulted in molybdenum chalcogenide nanoribbons including Janus MoSSe; a species only synthesised as a monolayer previously. ChemTEM, a process of the TEM electron beam simultaneously imaging a material whilst also providing energy to the system, was employed for studying the structures of synthesised tungsten disulfide nanoribbons within SWNTs and boron nitride nanotubes (BNNTs). Within SWNTs, the ejection of individual atoms and atomic chains were witnessed and promoted using the electron beam, resulting in the formation of a one atom thick nanowire which was characterised by contrast analysis. A BNNT containing amorphous material was imaged using AC-HRTEM; the electron beam was found to stimulate crystallisation and growth of tungsten disulfide quantum dots size-templated by the BNNT inner channel. Metal chalcogenide nanomaterials within SWNTs were tested as electrocatalysts towards the Hydrogen Evolution Reaction and found to perform well compared to larger nanostructures formed previously. This was a result of the SWNTs templating the formation of nanostructures with a high proportion of catalytically-active edge atoms, and being able to transport electrons to and from the guest species.